Teamwork Strengthening Strategies in Islamic Educational Leadership - Mia Audina; M. Sirozi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
School as a part of the organized education system is inseparable from management systems, where the school principal, as a leader in the educational institution, playsa role in directing human resources within the institution to coordinate and collaborate (teamwork). Teamwork is the best way to achieve organizational goals (educational institution). The school principal is developing a teamwork strengthening strategy that includes Building a Shared Vision, Facilitating Training and Team Building Workshops, Holding Regular Meetings and Periodic Evaluations, Creating a Positive Work Environment, Delegating Tasks Based on Expertise, Setting an Example in Leadership, Providing Recognition and Acknowledgment, Using Technology to Support Collaboration, Facilitating Open Communication, and Fostering Togetherness through Non-Formal Activities. The information for this research was collected through the Literature Review method, which concluded that Teamwork is the best way to achieve organizational goals (educational institutions).